A whole of systems approach to improved understanding of the environmental, economic and social values of a frontier marine oil and gas field: Establishment, success factors and lessons learnt. (November 2018) - Smith, David C.; Begg, Gavin A.; Lukatelich, Rod; Anson, Tim; Baghurst, Ben; Ham, Jane; Lapidge, Steven; Lewis, Rob; Ormandy, Phillipa; Smith, Rochelle; Ward, Tim
Abstract: The Great Australian Bight is one of Australia's most valuable marine ecosystems supporting globally significant populations of marine mammals, seabirds, and diverse and highly endemic benthic assemblages, as well as important fishing, aquaculture and ecotourism industries. The region is also considered a significant frontier for potential offshore petroleum resources and is actively being explored for oil and gas. The Great Australian Bight Research Program (GABRP) was an innovative, multi-year, 20 million, inter-disciplinary research collaboration involving BP Developments Australia (BP), CSIRO, the South Australian Research and Development Institute (SARDI), the University of Adelaide and Flinders University, that was developed in response to exploration activities in the region. The Program was the first large-scale, integrated study of the Great Australian Bight that involved more than 100 of Australia's leading scientists to generate a whole-of-system understanding of the region's environmental, economic and social values. We outline the processes to establish this strategic research collaboration, identify the key areas for success, and critically the lessons learned in order to guide future initiatives in regions open to exploration and development. As a result of the GABRP, there is now a legacy of data, information and models to inform future sustainable development in the Great Australian Bight; leading to the region now being one of the better understood deep water Australian marine systems.